pengembangan media KAMIDO berbasis metode Make a Match untuk meningkatkan penguasaan mufradat siswa kelas 8 di MTsN 4 Banda Aceh - Nurul Izzah; Mukhlisah; Rika Putri Rambe; Muhammad Akhyar (Tarling : Journal of Language Education, 2026)
This study aims to develop and examine the effectiveness of the Doraemon’s MagicPocket (KAMIDO) learning media using the Make a Match method to enhanceArabic vocabulary mastery among seventh-grade students at MTsN 4 Banda Aceh.This research employed the Research and Development (R&D) approach usingthe ADDIE model, which consists of five stages: Analysis, Design, Development,Implementation, and Evaluation. The research subjects were 30 seventh-gradestudents. The instruments used included interviews, observations, tests, anddocumentation. Media validation was conducted by material and media experts,yielding results of 96% and 92%, respectively, which fall under the “highly feasible”category. The effectiveness test used the One Group Pretest-Posttest Design. Dataanalysis revealed a significant improvement between the pretest score (45.50) andposttest score (88.00). The Paired Sample t-test result showed a significance value(Sig. 2-tailed) of 0.000 < 0.05, indicating a significant difference. The N-GainScore value of 0.78 or 78.69% falls into the “effective” category. Based on thesefindings, the KAMIDO learning media combined with the Make a Match methodproved to be effective, engaging, and suitable for teaching Arabic vocabulary,particularly in educational environments with limited technological resources